Does war destroy business? A review of empirical publications. Issue 1 (5th January 2023) - Naseem, Imran; Akbar, Saeed; Tahir, Muhammad; Imran, Saima
Abstract : The study investigates the economic dimensions of war. It considers empirical literature through structure review to explore the different effects of war on businesses. The scope of the study covers all geographical areas and studies dealing with any respective event in the 20 th and 21 st centuries. However, the study caters for quality, relevance, and recentness in publications. Hence, publications in 4*, 4, and 3 stars journals that are placed in Association of Business Schools of UK Guidelines in 2015 are reviewed. The study with its extant literature presents an important realization that against the stereo‐typed opinion about war being devastating to businesses indicates that war affects in various dimensions, that is, positive, negative, or even no effects depending on the nature and place of business. Whereas businesses, in general, may be negatively affected in wartime, businesses critical to war may get an unprecedented boost. The study also indicates a dire need of developing a framework for investigating this important relationship on sound footings.